PENGEMBANGAN MATERIAL PASAK ENDODONTIK Ti/40HA DENGAN MENGGUNAKAN KONSEP FUNCTIONALLY GRADIENT MATERIAL - M. K. Herliansyah (Universitas Gadjah Mada, 2013)
Commercial endodontic pegs have a homogeneous composition and strength so that the transmission voltage of pegs to dentin often result in damage to the tooth root. The concept of functionally gradient material (FGM) is expected to overcome these problems by adjusting the mechanical properties of each peg to the nature of the teeth. This study aims to develop a material stake with the concept of FGM from Ti/40HA material that is composed of five layers with concentrations of HA from 0% - 40% wt through the process of uni-axial pressing followed by sintering at 1200oC and 1400oC in argon gas. Then performed on each layer characterization by SEM / EDX, the optimum sintering temperature was determined by test-t (p <0,05). Morphological Testing showed that the composite of Ti/40HA still porous, while EDX shows the composition of Ca and P increase as an indication of increment in the concentration of HA as the decrement in concentration of the layer-1 (100% Ti) up to layer-5 (60% Ti-40% HA). In conclusion, Ti/40HA200 and Ti/40HA200 composite materials can be produced by decreasing its roughness as the rising concentrations of HA in each section.